Quality systems and business performance: case study in meat producing companies in a region of northwestern México - Huerta-Dueñas, Michaelene (2016)
In this article an exploratory analysis of the measurement of use of quality systems and their implications in business performance is done, taking as reference a case study in four meat producing companies of a Northern Mexican County. The main contribution of this work is based on a mixed methodology analyzed by means of the Preferential Weighting of Criteria. The results thread coincidences with other investigations, that conclude that quality systems increase enterprise performance in the productions and sales amounts.